Korkyt ata and shamanic values (Journal of Philosophy Culture and Political Science, 2021)
This article examines shamanism as an ancient religion and reveals the secrets of the faith healer shaman, who owns all magical rituals andinfluence of shamanic music and the special nature of kobyz sounds. The connection between ancient forms and meanings included in the anthropomorphic structure of the kobyz structure considers in sacred form. The etymological aspects of the concepts of shaman and kobyz are revealed, preserving the linguistic and semantic features of the worldview of the Kazakh people. The paper’s findings support a dissociative continuum that includes not only dissociation, but also integrity in relation to spirituality and expanded consciousness. We consider Korkyt Ata as a shaman, and evidence for this is his kobyz that holds Korkyt Ata. The main idea of the legends about Korkyt Ata rely on the idea of shamans, the idea of shamanism in general. The most ancient types of creators and keepers of Kazakh folklore by genesis are shamans.The article uses methods such as generalization, description, analysis, generalization and interpretation.Key words: culture, culture text, symbol, value, cultural-semiotic construction.